THE CORRELATION BETWEEN STUDENTS’ CRITICAL THINKING SKILL AND THEIR SPEAKING ABILITY AT STKIP ABDI PENDIDIKAN PAYAKUMBUH - Hervina, Hervina (ELP (Journal of English Language Pedagogy), 2023)
The success of speaking ability is influenced by various factors, and one of them is students' critical thinking. The application and improvement of students' critical thinking skills in learning English are considered important. This study aims to examine the correlation between students' critical thinking skills and their speaking ability. The researcher employed a quantitative approach using the correlation method. The sample consisted of students from STKIP Abdi Pendidikan Payakumbuh enrolled in the academic years 2017, 2018, and 2019. Questionnaires were distributed to 25 students to assess their critical thinking skills, while a speaking test was used to evaluate their speaking ability. The collected data were subjected to a normality test, revealing that the critical thinking skills data were normally distributed, whereas the speaking ability data were not. Data analysis was conducted using the Spearman-rho test in SPSS 2016. The obtained results showed that the significance value was 0.536 (> 0.05), and the coefficient score was 0.133 (< 0.2). Therefore, this study found no significant correlation between students' critical thinking skills and their speaking ability. Consequently, the alternative hypothesis (Ha) is rejected, while the null hypothesis (Ho) is accepted. Based on the result, it was not relation for English students departtment of STKIP Abdi Pendidikan to enhance their speaking abilty with critical thinking, but the students realize that one of factors of speaking is critical thinking.